Validação das intervenções de enfermagem para o diagnóstico de mobilidade física prejudicada nos lesados medulares - Leonardo Tadeu de Andrade (2007)
This is a descriptive study to validade the nursing interventions proposed in Nursing Interventions Classification (NIC) for the nursing diagnosis of impaired physical mobility by the nurses who work with the rehabilitation of adults with sequels for medullar lesion at rehabilitation hospitals. The method used was the intervention of use validation which is based on opinions of experts about a certain intervention, whether it is essential or not for the nursing dignosis of impaired physical mobility. Data was collected using a semi structured questionary given to 54 nurses at rehabilitation hospitals in Belo Horizonte, Fortaleza, Salvador and São Luis, Brazil. As results, among 46 nursing interventions described and suggested by the NIC, 17 (37%) interventions are essential and subject to be implemented, other 15 (32,6%) interventions were considered complementary and 14 (30,4%) interventions were considered not used and subject to be discarded. The nursing interventions not described at NIC to solve the nursing diagnosis of impaired physical mobility and reconmended by 22 experts (40,7%) were care with orthoses: maimtainance and care with orthoses: prevention. As a result, it is possible to conclude that the nursing interventions include prevention levels, promotion, maintainance and rehabilitation, aiming the obstruction of morbidities to instal giving the medular injured people a better life quality and a well being condition. The use of NIC method to validate a nursing interventions is adequate. Itis suggested that studies using nursing classifications as NIC clinical on various situations and with nurses from different specialities must be requered and stimulated.